Synthesis of Nanostructured Copper-doped Titania and Its Properties - Zuas, Oman; Budiman, Harry (Nano-Micro Letters, 2013)
Nanostructured pure-TiO2 and Cu3%-TiO2 were successfully synthesized via co-precipitation method. The X-ray diffraction (XRD) result proves that the synthesized sample were predominantly in anatase phase with size in the range of 8∼16 nm, which are in good agreement with the transmission electron microscopy data. Owing to doping of copper, not only did the thermal stability of the TiO2 decrease, but also a significant decrease in its particle size and a shift of the adsorption edge to a higher wavelength region appear. The activity of both pure-TiO2 and Cu3%-doped TiO2 was tested to study their ability to decolorize congo red (CR) dye in aqueous solution. We observed that the CR dye was decolorized faster by Cu3%-TiO2 than pure-TiO2. Results of this study demonstrate a potential application of the synthesized sample for decolorizing dye pollutants from aqueous waste.